Massive Spread of OXA-48 Carbapenemase-Producing Enterobacteriaceae in the Environment of a Swiss Companion Animal Clinic - Kira Schmitt; Michael Biggel; Roger Stephan; Barbara Willi (MDPI AG, 2022)
Background: Companion animal clinics contribute to the spread of antimicrobial resistant microorganisms (ARM) and outbreaks with ARM of public health concern have been described. Methods: As part of a project to assess infection prevention and control (IPC) standards in companion animal clinics in Switzerland, a total of 200 swabs from surfaces and 20 hand swabs from employees were collected during four days in a medium-sized clinic and analyzed for extended spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-E), carbapenemase-producing Enterobacteriaceae (CPE), vancomycin-resistant enterococci (VRE), and methicillin-resistant staphylococci (MRS). Results: A total of 22 (11.0%) environmental specimen yielded CPE, 14 (7.0%) ESBL-E, and 7 (3.5%) MRS; MR Staphylococcus aureus were isolated from two (10.0%) hand swabs. The CPE isolates comprised Escherichia coli, Klebsiella pneumoniae, Enterobacter hormaechei, Citrobacter braakii, and Serratia marcescens. Whole genome sequencing revealed that all CPE carried closely related blaOXA-48 plasmids, suggesting a plasmidic spread within the clinic. The clinic exhibited major deficits in surface disinfection, hand hygiene infrastructure, and hand hygiene compliance. CPE were present in various areas, including those without patient contact. The study documented plasmidic dissemination of blaOXA-48 in a companion animal clinic with low IPC standards. This poses a worrisome threat to public health and highlights the need to foster IPC standards in veterinary clinics to prevent the spread of ARM into the community.